TPM can go beyond maintenance: excerpt from a case implementation - Ahmed, Shamsuddin; Masjuki, Haji Hassan; Taha, Zahari (Emerald, 2005)
Purpose - The aim of this paper is to present a generic model on using the total productive maintenance (TPM) concept in conjunction with ecology oriented manufacturing (EOM) and 5S focusing on their joint strengths in attaining organizational goals in furtherance to the equipment maintenance objectives. Design/methodology/approach - A systematic implementation-framework coupled with the standard tools, techniques and practices has been designed. The framework was applied in a large semiconductor manufacturing company. Findings - It is evident that a well drawn TPM implementation plan not only improves equipment efficiency and effectiveness but also brings appreciable improvements in other areas such as reduction of manufacturing cycle time, size of inventory, customer complaints, and creates cohesive small group autonomous teams and increases the skill and confidence of individuals. The resulting system is found to be more productive in terms of both partial and total productivity measures. This is in line with the current need of manufacturing companies to have an integrated manufacturing management system (IMMS) in order to simultaneously increasing efficiency and improving effectiveness. Practical implications - The applied framework can be mimicked by other manufacturing organizations and similar results could be brought about. As the implementation of TMP in conjunction with the EOM and 5S has come out successful, this can be combined with other manufacturing planning and control (MPC) systems (viz. JIT, MRPII/ERP) to develop an IT-based IMMS. Originality/value - The case study presented here shows that the applications of TPM through the fulfillment of its basic requirements can significantly enhance the accomplishment of organizational objectives beyond the equipment maintenance-subsystem goals and add an array of benefits in the value chain across the various functional areas. © Emerald Group Publishing Limited.